Using Reverse Mentoring to Transform In-Service Teachers' Beliefs About How to Teach English - Liliana Valle; Danilsa Lorduy-Arellano; Nohora Porras-González (Universidad Nacional de Colombia, 2022)
This qualitative research study delves into elementary school teachers' beliefs and the potential contribution of reverse mentoring to improve English language teaching for children. The purpose was to explore how elementary in-service teachers' beliefs could be transformed after participating in a reverse mentoring experience. A group of in-service teachers from two public elementary schools and a group of student-teachers from Universidad de Córdoba (Colombia) were the research participants. Data were gathered through a questionnaire, interviews, and classroom observations. Findings showed that reverse mentoring played an important role in transforming in-service teachers' beliefs about teaching English to children regarding the difficulties of language learning, communicative strategies, motivation and expectations, foreign language aptitude, and the nature of language learning.